Force Based Design and Direct Displacement Based Design for Dual System Structure - Annisaa Dina Puspita; Anis Rosyidah (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
The Force Based Design (FBD) and the Direct Displacement-Based Design (DDBD) are methods for designing seismic-resistant buildings. Building structures designed, are expected to be suitable with the purpose and usefulness of a building. For this reason, this study compares the performance of dual system structures using the DDBD and FBD methods that aim to prove better performance with consideration of safety against users during an earthquake. This research method uses design analysis method to compare the value of the base shear force, reinforcement ratio, and performance level using software for static nonlinear pushover analysis. The results showed the value of the base shear force x direction of the DDBD method was 17.57% smaller than the FBD method, whereas for the y direction the DDBD value was greater than 9.38% of the FBD. The value of the reinforcement ratio of the beam, column and shear wall results is greater DDBD than FBD. The actual drift of the DDBD and FBD methods is slightly different. So that both are at the same level of performance, namely damage control. The performance level has not reached the performance target of life safety design in DDBD, but the structure has met the level performance requirements for offices.